-7p-18=-8p

Simple and best practice solution for -7p-18=-8p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7p-18=-8p equation:


Simplifying
-7p + -18 = -8p

Reorder the terms:
-18 + -7p = -8p

Solving
-18 + -7p = -8p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '8p' to each side of the equation.
-18 + -7p + 8p = -8p + 8p

Combine like terms: -7p + 8p = 1p
-18 + 1p = -8p + 8p

Combine like terms: -8p + 8p = 0
-18 + 1p = 0

Add '18' to each side of the equation.
-18 + 18 + 1p = 0 + 18

Combine like terms: -18 + 18 = 0
0 + 1p = 0 + 18
1p = 0 + 18

Combine like terms: 0 + 18 = 18
1p = 18

Divide each side by '1'.
p = 18

Simplifying
p = 18

See similar equations:

| 12x^2+42=15x^2+15 | | xcubed+xsquared=100 | | 4/5=x/4 | | -3(-7x+1)-2x=-22 | | dx/d | | 17-j=9 | | y+100=10x | | 5m-3m=10 | | 4c^2-56x+172=0 | | y-f/d | | 3.5x=50-5x | | -5s=20-10s | | 3/x=2/3 | | 14u=15u-20 | | x^2+5x-9x-45= | | X^2=9+81 | | 1x^2=3 | | 12x-12x-1=-3 | | log(x+1)-2logx=1 | | b-8.4=-29 | | -8x-8+4(x-2)=-3x+2 | | 27/8*10/3 | | 27/8(10/3) | | 2*(x+5)=-1 | | 2(1-2x)=4x+5 | | -6g=66 | | x^2+6x+2x+12= | | x+15=123 | | 5-8i= | | b+7=3b+2 | | 14=x-2*3 | | -4(3x-6)+2=-12x+26 |

Equations solver categories